RETRACTED: Genotypic investigation of drugs resistance and biofilm genes among ciprofloxacin-resistant Pseudomonas aeruginosa isolated from burn patients - Al-Salami Mohammed Abbas Farman; Tuwaij Nabil Salim Saaid (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001